Mengapa Akuntansi Syariah? Studi Interpretif terhadap Preferensi Mahasiswa - Meutia, Inten; Isnaini, Padilah; Yuniarti, Emylia (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
This study aimed to understand the accounting department students interest in choosing Islamic accounting course, especially the accounting students at Faculty of Economics, University of Sriwijaya. This study used phenomenology in the domain of interpretive paradigm to explore factors that motivate students to choose or not to choose Islamic accounting courses. The attribution theory was used to identify whether student motivation is determined by internal drive or external drive. The number of informants in this study was twelve students consisting of six students who choosed the subject of Islamic accounting and six students who did not choose the Islamic accounting course. The research findings showed that Islamic accounting course is mainly selected by students whose carrier plan in Islamic accounting. Students who have internal locus of control tend to make choices based on in order motive, while students who have external locus of control tend to make choices based on because of motive.